Affimers as anti-idiotypic affinity reagents for pharmacokinetic analysis of biotherapeutics - Adamson, Hope (BioTechniques, 2019)
Therapeutic antibodies are the fastest growing class of drugs in the treatment of cancer, and autoimmune and inflammatory diseases that require the concomitant development of assays to monitor therapeutic antibody levels. Here, we demonstrate that the use of Affimer nonantibody binding proteins provides an advantage over current antibody-based detection systems. For four therapeutic antibodies, we used phage display to isolate highly specific anti-idiotypic Affimer reagents, which selectively bind to the therapeutic antibody idiotype. For each antibody target the calibration curves met US Food and Drug Administration criteria and the dynamic range compared favorably with commercially available reagents. Affimer proteins therefore represent promising anti-idiotypic reagents that are simple to select and manufacture, and that offer the sensitivity, specificity and consistency required for pharmacokinetic assays